(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
In today’s globalization environment, English has become an important tool for international communication, science, technology, diplomacy and business. Therefore, the content and quality of English teaching in the education system is becoming an increasingly urgent issue. Unlike traditional teaching methods, modern requirements require an English teacher not only to know the grammar and methodology of the language, but also to be able to positively influence the psychological state, personal development and social adaptation of students. An important component of such potential is the teacher’s emotional intelligence.